2021
DOI: 10.35608/ruraled.v42i2.1244
|View full text |Cite
|
Sign up to set email alerts
|

What We Know and Where To Go: A Systematic Review of the Rural Student College and Career Readiness Literature and Future Directions for the Field

Abstract: College and career readiness has become a national education policy priority. With more than 9.3 million rural students in the United States, the college and career readiness of rural students is a warranted priority for rural education researchers. Using a combination of Conley’s (2012) college and career readiness model, Perna’s (2006) nested model of college choice, and Social Cognitive Career Theory (Lent et al., 2014), we systematically reviewed and analyzed the extant literature on rural students’ colleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…When describing aspects of career development work that challenge them, the participants described how the lack of caregiver support can stymie their career development efforts, as noted in the first theme. As mentioned, caregivers are key allies in supporting rural students’ career development (Agger et al, 2018; ASCA, 2023; Roberts & Grant, 2021; Slocum et al, 2020). Most parents are, indeed, highly supportive of students’ postsecondary goals, but some simply may not possess the knowledge of complexities related to the postsecondary planning process (Cholewa et al, 2015), which may be particularly true for first-generation rural students (Slocum et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When describing aspects of career development work that challenge them, the participants described how the lack of caregiver support can stymie their career development efforts, as noted in the first theme. As mentioned, caregivers are key allies in supporting rural students’ career development (Agger et al, 2018; ASCA, 2023; Roberts & Grant, 2021; Slocum et al, 2020). Most parents are, indeed, highly supportive of students’ postsecondary goals, but some simply may not possess the knowledge of complexities related to the postsecondary planning process (Cholewa et al, 2015), which may be particularly true for first-generation rural students (Slocum et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Chambers and colleagues (2019) found a positive relationship between teacher support and students’ postsecondary aspirations, and Tieken (2016) found that both rural teachers and school counselors encouraged students to pursue in-demand postsecondary pathways. Like school staff, family and community ties are vital considerations related to career development in rural settings (Carrico et al, 2019; Petrin et al, 2014; Roberts & Grant, 2021; Slocum et al, 2020). In many rural settings, these constituents support students’ postsecondary decision-making in several forums, such as schools, civic organizations, and religious organizations.…”
Section: Rural School Counseling and Career Developmentmentioning
confidence: 99%
“…Given these benefits, the high degree of personal, familial, and institutional investment in the four-year baccalaureate degree as a normative ideal is understandable. However, in rural areas, the emphasis on college attendance also has been criticized as a "talent extraction mechanism" that depletes human capital and promotes a sense of uprootedness (Roberts and Grant, 2021;Tran and DeFeo, 2021), making postsecondary planning complicated for individuals and perilous for communities due to the "mobility imperative" collegegoing typically introduces (Farrugia, 2016). These factors create different normative pressures on youth future planning that are important to understand.…”
Section: Introductionmentioning
confidence: 99%
“…While acknowledging differences within rural communities and being mindful to avoid a deficitbased approach, it remains important to highlight some overarching mindsets and values that have been shown to impact rural student trajectories. Families play an instrumental role in shaping both educational and career-related decisions (Hudacs, 2020;Nelson, 2019;Roberts & Grant, 2021). Unity, as well as care and concern for community, also play a vital role (Li, 2019;Peterson, 2020).…”
Section: Rural Mindsets and Valuesmentioning
confidence: 99%
“…For instance, institutions can lean into the close-knit ties of rural students by acknowledging the influences that students already have and are already actively utilizing for support. Several successful college access programs have brought parents and communities into the process of the college decision (McCulloh, 2022;Roberts & Grant, 2021;Tieken, 2020). Tieken (2020) recommends intentionally encouraging whole-family education and discussion about the college decision-making process.…”
Section: Successful Rural College Access and Pre-college Career Devel...mentioning
confidence: 99%